MECHANISMS OF THE POLITICAL AGREEMENT ACHIEVING: A COMPARATIVE ANALYSIS - Ростецька, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted to the theoretical and practical problems of the political agreement achieving in the conditions of the modern political process. The comparative analysis of the political agreement achieving mechanisms was completed.